Double-Stranded RNA Methods and Protocols - Cheng, Xiaofei (Methods in Molecular Biology, 2025)
This detailed volume examines classical and cutting-edge methods involving double-stranded RNA (dsRNA), specifically regarding isolation, visualization, characterization, production, and application. Many protocols, such as co-immunoprecipitation-based isolation of double-stranded RNA-associated protein complexes, identification of mycoviruses by dsRNA extraction, application of dsRNA for fungi disease management (Sclerotinia sclerotiorum and Botrytis cin), and production of double-stranded RNA in plants by plant viral vectors for gene silencing, can also be easily adapted for identification of viruses from other organisms, control of other pathogens, and fundamental research. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step and readily reproducible laboratory protocols, as well as tips for troubleshooting and avoiding known pitfalls. Reliable and practical, Double-Stranded RNA: Methods and Protocols serves as an ideal reference book for students and researchers who work with dsRNA.